KESEHATAN BIBIT TANAMAN PULAI (Alstonia scholaris) DI BALAI PERBENIHAN TANAMAN HUTAN (BPTH) DINAS KEHUTANAN PROVINSI KALIMANTAN SELATAN - Devi Satiti; Susilawati Susilawati; Dina Naemah (Jurnal Sylva Scienteae, 2023)
The purpoose of the study was to analyze te health condition of pulai (Alstonia scholaris) seedlings based on the damage caused by pests and diseases through the appearance of damage to the stems, shoots, leaves and branches and calculate the percentage of damage to pulai (Alstonia shcolaris) seedlings through the Environmental Monitoring and Assessment Program method. EMAP). This research was carried outt at the Forest Plant Seed Center (BPTH) of the Province of South Kalimantan. This researrch was carried out for ± 2 months starting from April to June which includes the stages of research preparation, data collection, data processing and analysis, to writing research reports. The implementation in this research has several stages, namely: Observation or Location Observation, Preparation of Tools and Materials and Data Collection. The selection of the type of seed that wil be the object of reesearch is 50% for the sample. Sampling used a random method or Systematic random sampling, namely the sampling technique was carried out with a sample frame arranged randomly in beds of 1,445 seeds which were numbered and extracted up to 700 numbers and the sample taken was a random meethod. Observing 1 by 1 sample based on the provisions contained in the EMAP classification. The resullts of the research, namely the analysis showeed that the causes of damage consisted of 5, namely due to death, insects, disease, human activities, and plant competition with the damaged parts of the seeds found in the shoots and leaves. The types of damage consisted of dead shoots, damaged leaves, and changes in leaf color and the highest severity is in the range of 30-39%. The ranking of the biggest damage was caused by insects on the leavess and the percentage of damage to stems of pulai (Alstonia Scholaris) was 41.43%.Tujuan penelitian untuk menganalisis kondisi kesehatan bibit pulai (Alstonia scholaris) berdasarrkan kerusakan yang disebaabkan oleh hama dan penyakit melalui kenampakan kerusakan pada bagian batang, pucuk, daun dan cabang dan menghitung persentase kerusakan bibit pulai (Alstonia shcolaris) melalui metode Enviromental Monitoring And Assesment Program (EMAP). Pelaksanaan dallam penelitian ini terdapat beberapa tahapan, yaitu: Observasi atau Pengamatan Lokasi, Persiapan Alat dan Bahan dan Pengambilan Data. Jenis bibit yang dipilih sebesar 50% untuk dijadikan sampel. Pengambilan sampel menggunakan cara acak atau Systematic random sampling dengan kerangka sampel (sample frame) yang disusun secara acak dalam bedengan sebanyak 1.445 bibit yang diberi nomor dan diekstraksi hingga 700 nomor dan sampel yang diambil adalah metode acak. Mengamati 1 per 1 sampel berdasarkan ketentuan yang terdapat pada klasifikasi EMAP. Hasil penelitian yaitu analisis menunjukkan bahwa penyebab kerusakan terdiri dari 5 yaitu  karena mati, serangga, penyakit, kegiatan manusia, dan persaingan tumbuhan dengan bagian bibit yang rusak terdapat pada pucuk dan daun.Tipe kerusakan terdiri atas pucuk mati,daun rusak,dan perubahan warna daun dan tingkat keparahan terbanyak berada dikisaran 30-39%. Ranking kerusakan terbesar adalah karena serangga di bagian daun dan persentase kerusakan batang pulai (Alstonia Scholaris) adalah 41,43%.